Vegetation analysis of the Taormina Region in Sicily: a plant landscape characterized by geomorphology variability and both ancient and recent anthropogenic influences - Sciandrello, Saverio; D'Agostino, Sonia; Minissale, Pietro (Lazaroa, 2013)
The vegetation composition and landscape analysis of the Taormina region (Messina, Sicily) in relation to anthropogenic influences was investigated. A total of 183 phytosociological relevés were performed in the period 2009-2012. Despite strong human influence, the area studied is characterized by the occurrence of several plant-communities, mainly represented by woods and shrubs vegetation (Quercion ilicis, Oleo sylvestris-Ceratonion siliquae), riparian woods and shrubs (Platanion orientalis, Rhamno-Prunetea), dry grasslands (Lygeo-Stipetea), hygrophilous communities (Molinio-Arrhenatheretea, Nasturtio-Glycerietalia and Isoeto-Nanojuncetea), rupicolous communities (Asplenietea trichomanis, Parietarietea judaicae), rocky coast communities (Crithmo-Limonietea), pasture coenosis (Poetea bulbosae), spring-flowering meadows (Tuberarietea guttatae and Stipo-Trachynietea distachyae) and nitrophilous communities (Onopordetea acanthii). The vegetation analysis allowed the identification of 34 vegetation types, with 8 new associations and 3 new sub-associations, and also allowed the reconstruction of the vegetation series and landscape units (geosynphytosociology). The synphytosociological analysis of the plant communities allowed the identification of the main vegetation series: climatophilous acidophilous series of metamorphic substrates (Erico arboreae-Querco virgilianae sigmetum); climatophilous basophilous series of sedimentary substrates (Oleo-Querco virgilianae sigmetum); edaphomesophilous series of the cliffs (Bupleuro fruticosi-Querco ilicis sigmetum); edapho-xerophilous series of the semirupestrian maquis (Euphorbieto dendroidis sigmetum); edafo-hygrophylous geoseries of the riparian wood (Platano-Salico gussonei sigmetum); and chasmophilous permaseries of the cliffs (Erucastro virgati sigmetum, Limonio ionici sigmetum). Overall, this territory should be considered an area of remarkable geobotanical significance, which still shows interesting vestiges of natural vegetations and deserving of preservation.
Keywords: vegetation; synphytosociology; Peloritani Mountains; landscape; conservation; Sicily